Painel modular intertravado de matriz cimentícia com reforço estrutural de bambusa vulgaris - Gomes Neto, José Augusto (2017)
Among the plant materials that have potential to be applied in construction, stands out the bamboo. It is a renewable material, which presents energy efficiency and adequate mechanical strength that allows the development of new eco-efficient building systems. In this study it was sought to develop modular precast panels of cementitious matrix within which there are culms of Bambusa vulgaris. These panels, 10 cm thick and 40 cm wide, have the height calculated so as to have the minimum height allowed by municipal legislation, i.e. 2,60 m. The cement matrix was composed of a Portland cement mortar, sand, lime, as well as coconut fibers and, in order to reduce the weight and the consumption of cement, Ethylene Vinyl Acetate (EVA) from waste from the manufacture of footwear. Bamboo culms of the specie under study were characterized by physical (mechanical properties, density, moisture content, water absorption in various conditions, dimensional variations and geometrical properties) and mechanical tests (compressive strength, tensile and shear strength, all parallel to the fibers). In order to reach the structural panels, several tests were carried out on small scale panels, 10 cm thick, 20 cm wide and 40 cm high. The main objective was to control the cracking that tends to occurs parallel to the culms. Two life-size panels were constructed and tested on structures laboratory. They were instrumented with displacement meters and subjected to increasing load until rupture. The panels presented suitable structural performance, reaching a maximum equivalent linear load of at least 300 kN / m, which qualifies them for use in buildings of more than one floor.